A mini review on solar energy based pumping system for irrigation. (2021) - Singh, Desh Bandhu; Mahajan, Anmol; Devli, Divyansh; Bharti, Kiran; Kandari, Shashank; Mittal, Gaurav
Abstract: Solar energy has the potential to meet the requirement of energy for the survival of human beings on the planet earth if used wisely. Some of the applications consist of electric power generation with the help of solar panel/thermoelectric generator/Rakine cycle based technology, water purification, dryer for agriculture product and refrigeration. Solar energy is pollution free and it can be utilized for irrigation with the help of solar energy based pump and some system for distribution of water. Many solar energy based pumping systems have been reported by researchers around the globe. In this work, a review on solar energy based pumping systems has been presented. Based on the study, conclusions have been drawn.